Maternal Serum Glycosylated Fibronectin as a Point-of-Care Biomarker for Assessment of Preeclampsia. Issue 4 (December 2015) - Rasanen, J.; Quinn, M.J.; Laurie, A.; Bean, E.; Roberts, C.T.; Nagalla, S.R.; Gravett, M.G.
Abstract : ( Am J Obstet Gynecol. 2015;212:82.e1–82.e9)